Analysis of Human Resource Development and Work Motivation in Improving Service Quality at JNE Agent Villa Dago Pamulang - Isnaeni, Devi Putri; Marlinah, Henni; Gunawan, Hendri (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to find out the human resource development that has been carried out in an effort to improve the quality of service at JNE Agent Villa Dago Pamulang, what efforts have been made so far to increase employee work motivation at JNE Agent Villa Dago Pamulang, Obstacles in developing human resources and work motivation in improving the quality of service at JNE Agent Villa Dago Pamulang. This study uses a qualitative descriptive approach. Data collection techniques are in the form of interviews, observations, and documentation. The result of this research is that the development of human resources at JNE Agent Villa Dago Pamulang has been carried out well, namely through training at the agent and at the center, providing briefings through training and during briefings and helping employees who experience difficulties while working. The efforts made at JNE Villa Dago Pamulang Agent are by providing services in the form of appropriate wages or salaries, by trying to create comfortable and harmonious working conditions for employees, providing adequate facilities. The obstacle in developing human resources and work motivation at JNE Agent Villa Dago Pamulang is the number of similar competitors with their respective advantages and employee personalities that need to be improved again in order to serve consumers well.